Climate‐induced hydrological variation controls the transformation of dissolved organic matter in a subalpine lake. (12th January 2018) - Ejarque, Elisabet; Khan, Samiullah; Steniczka, Gertraud; Schelker, Jakob; Kainz, Martin J.; Battin, Tom J.
Abstract: Lakes are an inherent component of the global carbon cycle. They receive dissolved organic matter (DOM) from the catchment, which is stored, transformed and respired, or delivered downstream. In this study, we show that a subalpine lake shifts its role from DOM "transporter" to "transformer" depending on season and climate. We monitored dissolved organic carbon (DOC) concentration and DOM optical properties at the inlet and outlet of subalpine Lake Lunz (Austria) at high frequency during two contrasting years: an extreme drought in 2015, and regular precipitation regime in 2016. During both years, the DOC mass balance revealed that inflowing and outflowing DOC loads were nearly balanced (+6.57% and +1.70% DOC production in 2015 and 2016, respectively). However, DOM optical properties revealed an in‐lake turnover of DOM compounds, so that the terrestrial and aromatic signature of inflowing DOM was modified into autochthonous, protein‐like DOM. The magnitude of this transformation varied seasonally, being maximal in summer and minimal in winter, presumably following periods of high and low primary production and photo‐degradation. Inter‐annually, we found that drought further increased DOM transformation during summer by extending the lake water residence time. Finally, our results demonstrate a rapid response of DOM dynamics to hydrological and meteorological changes at both seasonal and inter‐annual scales, suggesting that carbon cycling in clear‐water mountain lakes may be highly sensitive to hydrological variation.